(untitled) (Educação e Pesquisa, 2000)
This work deals with the trajectory of the administrative orientations and practices of a Portuguese school headmaster between the mid 1950s and the mid 1970s. By doing that, a better understanding is sought for the circumstances, processes and meanings that characterized in that period the trajectory of the Portuguese school system itself, and particularly with respect to the expansion of mandatory schooling and to the unification of post-primary schooling. The text articulates six fragments from a larger investigation which took the shape of a historical-organizational case study in which the history of a group of teachers of a school discipline took form. The narratives presented result from the use of oral sources of information (interviews) and written ones (official documents, pedagogical press, teachers personal documents, school archives). The fragments presented here which acquire unity around the figure of the headmaster result also from the employment of micropolitical frameworks to the analysis of school everyday life. For this reason, phenomena related both to the coordination and to the disputes around ideological and material interests are highlighted, and so are the strategies engaged in the expansion or defense of autonomy limits in the control of the administrative work in schools. Stand out therefore the processes that elevated a school and its headmaster to the status of unique model within the Portuguese school network of that time.